Habituation or sensitization? Long-term responses of yellow-bellied marmots to human disturbance. (3rd April 2021) - Uchida, Kenta; Blumstein, Daniel T
Abstract: Continuous exposure to humans causes wildlife to either habituate or sensitize. Although increased tolerance may play an important role in coexistence with humans, the mechanisms and fitness outcomes of long-term changes of tolerance are not fully understood because only a few studies have assessed individual- and population-level responses over many years. We developed a novel predictive framework to study habituation and sensitization to humans and applied it to yellow-bellied marmots ( Marmota flaviventer ) in areas of high and low human disturbance. We focused on two antipredator behaviors—time allocation to vigilance during foraging to quantify baseline vigilance levels and flight initiation distance (FID)—to quantify subsequent responsiveness to threat. We used the rate of body mass gain during the active season as a fitness outcome. Assessing 15 years' population and individual-level responses to human disturbances, marmots in highly disturbed colonies allocated more time to vigilance, but this did not change over time. FID decreased on average when they were approached more and also tended to decrease in highly disturbed colonies and over 15 years. Yet, there was individuality in FIDs; marmots that fled at greater distances became sensitized with repeated approaches. Additionally, the marmots in highly disturbed colonies gained less body mass over time compared to conspecifics in less disturbed colonies. These results suggested that, although marmots habituated to humans, long-term human disturbance has negative fitness consequences. Our framework should help wildlife managers evaluate the comprehensive impact of human activities on wildlife. Abstract : We developed a novel framework to study habituation/sensitization in wildlife and assessed 15 years of yellow-bellied marmots' individual and population-level responses to human disturbance. While marmots tended to decrease responses directed to humans at the individual and population levels (i.e., they habituated to humans), they allocated more time to vigilance while foraging and decreased the rate of body mass gain over time in highly disturbed areas. This indicates that chronic human disturbance may have detrimental effects on individual fitness and potentially population dynamics.